Innovative Approaches for Immune Tolerance to Factor VIII in the Treatment of Hemophilia A - Sherman, Alexandra; Biswas, Moanaro; Herzog, Roland W. (Frontiers in Immunology, 2017)
Hemophilia A (coagulation factor VIII deficiency) is a debilitating genetic disorder that is primarily treated with intravenous replacement therapy. Despite a variety of factor VIII protein formulations available, the risk of developing anti-dug antibodies (“inhibitors”) remains. Overall, 20–30% of patients with severe disease develop inhibitors. Current clinical immune tolerance induction protocols to eliminate inhibitors are not effective in all patients, and there are no prophylactic protocols to prevent the immune response. New experimental therapies, such as gene and cell therapies, show promising results in pre-clinical studies in animal models of hemophilia. Examples include hepatic gene transfer with viral vectors, genetically engineered regulatory T cells (Treg), in vivo Treg induction using immune modulatory drugs, and maternal antigen transfer. Furthermore, an oral tolerance protocol is being developed based on transgenic lettuce plants, which suppressed inhibitor formation in hemophilic mice and dogs. Hopefully, some of these innovative approaches will reduce the risk of and/or more effectively eliminate inhibitor formation in future treatment of hemophilia A.